Method for judging solidification structure type of SPHC low-carbon steel slab

By cutting and grinding the sample, and using a mixed solution of deionized water and anhydrous copper chloride for heating corrosion, combined with optical microscope observation, the problem of difficult to determine the solidification structure type of SPHC low-carbon steel slabs is solved, and rapid Accurate organization type determination and performance improvement.

CN119290880APending Publication Date: 2025-01-10德龙钢铁有限公司 +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411479649.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

During the continuous casting of slabs, it is difficult to accurately determine the solidification structure type of SPHC low-carbon steel slabs, especially distinguishing columnar crystals and isometric crystals, resulting in deterioration of mechanical properties and the existing solution erosion conditions are not standardized, resulting in experimental errors and The operation error is large and the process parameters cannot be adjusted in time.

Method used

Heating corrosion is carried out using a mixed solution including cutting samples, grinding and polishing the surface, using deionized water and anhydrous copper chloride and 35% hydrochloric acid. The hydrochloric acid supplement is monitored through boiling state and weighing device to ensure the stable concentration of the corrosion liquid. Use optical microscope to observe dendrites' growth to clarify the solidified tissue type.

Benefits of technology

It realizes rapid and accurate determination of the solidification structure type of SPHC low-carbon steel slab, reduces experimental errors, is timely effective, can adjust process parameters in a timely manner, and improves the performance of the casting billet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005097005700000011
    Figure HDA0005097005700000011
  • Figure HDA0005097005700000012
    Figure HDA0005097005700000012
  • Figure HDA0005097005700000013
    Figure HDA0005097005700000013
Patent Text Reader

Abstract

A method for judging the solidification structure type of an SPHC low-carbon steel slab comprises the following steps that a sample is detached and cut into square blocks with the proper size, then the face needing to be observed is ground and polished, and then two sets of weighing devices and beakers are arranged and used for calculating the amount of hydrochloric acid needing to be supplemented; putting the sample into a mixed solution of deionized water, anhydrous copper chloride and hydrochloric acid with the concentration of 35%, heating for reaction, supplementing hydrochloric acid according to the reduction amount of hydrogen in the process to ensure the concentration, then taking out the eroded sample, washing with clear water, spraying alcohol on the surface of the sample after washing, and drying with a blower to prevent the surface of the sample from being oxidized and polluted; and finally, photographing the eroded sample, macroscopically showing the condition of the eroded surface, observing by using an optical microscope, checking the growth condition of dendritic crystals, and emphatically observing and recording a dendritic crystal change area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for determining the type of solidification structure of a SPHC low-carbon steel slab, in particular to a method capable of accurately determining the type of the solidification structure of the SPHC low-carbon steel slab, and belongs to the technical field of metallurgical continuous casting. Background Art

[0002] During the continuous casting of slabs, the molten steel gradually cools from liquid to solid, passing through water cooling in the crystallizer, spray cooling in the secondary cooling zone, and air cooling in the air cooling zone. Due to the presence of some alloys and a small amount of inclusions in the steel, these substances form heterogeneous nuclei and continue to grow when the molten steel solidifies, extending outward in the form of dendrites; columnar crystals are dominant near the edge of the ingot, with a fast cooling rate; mixed crystals are a non-equilibrium phenomenon due to differences in temperature and cooling time; the cooling rate of the molten steel in the center of the ingot is slow, and the temperature is relatively balanced, so the dendrites grow evenly to form an equiaxed crystal structure; in the solidified structure, the length of the columnar crystal is much greater than the width and Height, resulting in poor mechanical properties, controlling low-proportion columnar crystals and high-proportion equiaxed crystals is one of the important measures to improve the performance of the ingot; the microstructure erosion of low-carbon steel is difficult, and the solution erosion conditions are not standardized, such as heating time, solution ratio and other conditions are not uniform. In the actual erosion process, after multiple attempts, the internal structure of the ingot is still unclear, especially the boundary between columnar crystals and equiaxed crystals cannot be distinguished, and the different dendrites and white bright bands inside the ingot cannot be accurately judged; therefore, a method is needed to efficiently erode and obtain the solidification microstructure type of low-carbon SPHC steel ingot, to make an accurate judgment on the changes in dendrites in the ingot, so as to clarify the microstructure characteristics of each part of the ingot. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for determining the solidification structure type of a SPHC low-carbon steel slab, which can quickly and accurately determine the change of the solidification structure type; the experimental process and post-processing method of the method are standardized and innovative, and can better reduce experimental errors and operational errors; the method is time-effective, and the solidification structure can be observed after the experiment is completed, which is conducive to timely adjusting process parameters in actual production to obtain the desired solidification structure type.

[0004] The problem described in the present invention is solved by the following technical solutions: A method for determining the solidification structure type of a SPHC low-carbon steel slab comprises the following steps: Step 1: Cut the sample into square blocks, and then grind and polish the side of the sample that needs to be observed until the surface is bright, flat, and free of stains to prevent excessive or insufficient erosion of the sample during the experiment; Step 2: Place the heater on the first weighing device, and place the first beaker on the heater, place two sizes of small blocks at the bottom of the heater for support, so that the first beaker is tilted, and ensure that the protruding opening of the first beaker is located at the bottom of the upper edge of the first beaker, place the second beaker on the second weighing device, and then use a silicone hose to set the protruding opening of the first beaker, one end of the silicone hose is connected to the upper end of the condenser, and the bottom end of the condenser is located directly above the second beaker; Step 3: Place two small blocks of different sizes at the bottom of the sample to ensure that the polished surface of the top of the sample is horizontal after it is placed in the first beaker; Step 4: Add deionized water to the first beaker and heat it, then add anhydrous cupric chloride and 35% hydrochloric acid, stir evenly, and then put the sample into the mixed solution; Step 5: Use a heater to heat the first beaker, requiring the liquid surface to remain boiling for a period of time. During this period, copper chloride will undergo a replacement reaction with iron atoms, and a layer of copper film will be covered on the surface of the sample. The boiling mixed solution will take a long time to flush the copper film, causing it to break and expose the corrosion surface of the sample; calculate the difference in the quantities measured by the two weighing devices at regular intervals, and then calculate the amount of hydrochloric acid that needs to be added, and then add hydrochloric acid to the first beaker; Step 6: Take out the eroded sample and rinse it with clean water for more than 1 minute. After cleaning, spray alcohol on the surface of the sample and blow dry it with a hair dryer to prevent oxidation contamination on the surface of the sample; Step 7: Take photos of the eroded samples to show the corrosion surface conditions at a macroscopic level. Use an optical microscope to observe and check the growth of dendrites, and focus on observing the dendrite change area for recording. Starting from the edge of the ingot, the dendrites grow vertically along the inner-outer arc, and their solidification structure is columnar crystals until the dendrite growth direction deflects and breaks. If the columnar crystals develop inward and are interrupted by abnormal tissues, but the development direction of the columnar crystals remains unchanged, the abnormal tissues can be seen as white bright bands. At the center of the ingot, the columnar crystals completely disappear, and the solidification structure enters the equiaxed crystal zone.

[0005] In the above method for determining the solidification structure type of SPHC low-carbon steel slab, in step 4, the content of deionized water added to the first beaker is 200 ml. After the deionized water is heated to 50°C, 10 g of anhydrous cupric chloride and 100 ml of 35% hydrochloric acid are added to the first beaker and stirred until the mixed solution is uniform. After the sample is added to the heated mixed solution, the position is adjusted so that the top surface of the sample is horizontal, and the top of the first beaker is covered with a waterproof plate such as a glass plate or a silicone pad to cover the surface of the beaker. The protruding notch of the beaker is used as an exhaust and condensation outlet. The first beaker always maintains an overall high temperature atmosphere, thereby accelerating the overall erosion efficiency. At this time, the data displayed by the weighing device is recorded.

[0006] In the above method for determining the solidification structure type of SPHC low-carbon steel slab, in step five, when the heater heats the first beaker, the temperature of the mixed liquid in the first beaker is maintained above 80°C, and the heating time needs to exceed 30 minutes. The difference between the weight reduction measured by the first weighing device and the weight increase measured by the second weighing device is calculated every 10 minutes. This data difference is the weight of the lost hydrogen. The amount of hydrochloric acid required to be added is calculated based on the weight of the lost hydrogen, and then the hydrochloric acid is added to the first beaker to maintain the concentration of the corrosive solution as much as possible.

[0007] In the above method for determining the solidification structure type of SPHC low-carbon steel slab, in step 4, the distance between the top surface of the sample immersed in the mixed solution and the liquid surface of the mixed solution is at least 2 mm.

[0008] The present invention studies the composition of SPHC steel grades, and can perform corrosion analysis by electromagnetic stirring under different currents in the crystallizer. The ingot has good macroscopic and microscopic effects under the current of 0-300A, and the boundary between dendrite melting and breaking is obvious. After corrosion, the distribution, width and range of columnar crystals, equiaxed crystals and white bright bands on the surface of the ingot under different current intensities can be clearly identified. Secondly, the raw materials of the present invention are easy to obtain, and there is no need to use special chemical reagents for certain components. There are no chemical raw materials prohibited by the state. The experiment can be completed under indoor ventilation conditions, the operation process is not cumbersome, and the experimental results are significant; In the present invention, during the corrosion process, the top of the beaker is covered; during the heating process, hydrochloric acid not only reacts with the sample, but also participates in the volatilization process. This boiling effect is not caused by the boiling of the aqueous solution, but by the generation and floating of hydrogen. Therefore, the evaporated mist is condensed and diverted. At different stages, hydrochloric acid is added according to the proportion of the original corrosion solution according to the condensation amount to ensure that the hydrochloric acid concentration in the corrosion solution is relatively stable, thereby improving the corrosion effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is the sample pickling flow chart; Figure 2 This is the corrosion mechanism diagram of the corrosive solution; Figure 3 This is the macrostructure diagram of SPHC ingot of Example 1; Figure 4 This is the macrostructure diagram of the SPHC ingot in Example 2; Figure 5 It is a diagram showing the proportion of different solidification structures of Example 1 and Example 2; Figure 6 This is the broken columnar crystal near the white bright band in Example 1; Figure 7 This is the columnar crystal near the equiaxial crystal region in Example 1; Figure 8 This is the columnar crystal near the equiaxial crystal zone in Example 2. DETAILED DESCRIPTION

[0010] A method for determining the solidification structure type of a SPHC low-carbon steel slab comprises the following steps: Step 1: Cut the sample into square blocks, and then grind and polish the side of the sample that needs to be observed until the surface is bright, flat, and free of stains to prevent excessive or insufficient erosion of the sample during the experiment; Step 2: Place the heater on the first weighing device, and place the first beaker on the heater, place two sizes of small blocks at the bottom of the heater for support, so that the first beaker is tilted, and ensure that the protruding opening of the first beaker is located at the bottom of the upper edge of the first beaker, place the second beaker on the second weighing device, and then use a silicone hose to set the protruding opening of the first beaker, one end of the silicone hose is connected to the upper end of the condenser, and the bottom end of the condenser is located directly above the second beaker; Step 3: Place two small blocks of different sizes at the bottom of the sample to ensure that the polished surface of the top of the sample is horizontal after it is placed in the first beaker; Step 4: Add deionized water to the first beaker and heat it, then add anhydrous cupric chloride and 35% hydrochloric acid, stir evenly, and then put the sample into the mixed solution; Step 5: Use a heater to heat the first beaker, requiring the liquid surface to remain boiling for a period of time. During this period, copper chloride will undergo a replacement reaction with iron atoms, and a layer of copper film will be covered on the surface of the sample. The boiling mixed solution will take a long time to flush the copper film, causing it to break and expose the corrosion surface of the sample; calculate the difference in the quantities measured by the two weighing devices at regular intervals, and then calculate the amount of hydrochloric acid that needs to be added, and then add hydrochloric acid to the first beaker; Step 6: Take out the eroded sample and rinse it with clean water for more than 1 minute. After cleaning, spray alcohol on the surface of the sample and blow dry it with a hair dryer to prevent oxidation contamination on the surface of the sample; Step 7: Take photos of the eroded samples to show the corrosion surface conditions at a macroscopic level. Use an optical microscope to observe and check the growth of dendrites, and focus on observing the dendrite change area for recording. Starting from the edge of the ingot, the dendrites grow vertically along the inner-outer arc, and their solidification structure is columnar crystals until the dendrite growth direction deflects and breaks. If the columnar crystals develop inward and are interrupted by abnormal tissues, but the development direction of the columnar crystals remains unchanged, the abnormal tissues can be seen as white bright bands. At the center of the ingot, the columnar crystals completely disappear, and the solidification structure enters the equiaxed crystal zone.

[0011] In step 4, 200 ml of deionized water is added to the first beaker. After the deionized water is heated to 50°C, 10 g of anhydrous copper chloride and 100 ml of 35% hydrochloric acid are added to the first beaker and stirred until the mixed solution is uniform. After the sample is added to the heated mixed solution, the position is adjusted so that the top surface of the sample is horizontal. The top of the first beaker is covered with a waterproof plate such as a glass plate or a silicone pad to cover the surface of the beaker. The protruding notch of the beaker is used as an exhaust and condensation outlet. The first beaker always maintains an overall high temperature atmosphere, thereby accelerating the overall corrosion efficiency. At this time, the data displayed by the weighing device is recorded.

[0012] The hydrochloric acid reacts with the surface of the ingot for 2 hours. + +Fe=H 2 +Fe 2+ , anhydrous copper chloride undergoes a replacement reaction with the surface of the ingot, Cu 2+ +Fe=Cu+Fe 2+ , the corrosive solution boils and impacts the copper film, and the copper film is washed away to reveal the corroded surface; In step five, when the heater heats the first beaker, the temperature of the mixed liquid in the first beaker is maintained above 80°C, and the heating time needs to be more than 30 minutes. The difference between the weight reduction measured by the first weighing device and the weight increase measured by the second weighing device is calculated every 10 minutes. This data difference is the weight of the lost hydrogen. The amount of hydrochloric acid required to be added is calculated based on the weight of the lost hydrogen, and then the hydrochloric acid is added to the first beaker to maintain the concentration of the corrosive solution as much as possible.

[0013] It can be seen that hydrogen contains 2 hydrogen atoms and hydrochloric acid contains one hydrogen ion. Their respective molar masses are 2 and 36, so it takes 18 hydrochloric acids to consume 1 hydrogen atom, and 36 HCl for one hydrogen. The mass fraction of concentrated hydrochloric acid is between 35-37%, so the consumed hydrochloric acid needs to be divided by about 36%, which is the amount of hydrochloric acid solution added; In step 4, the distance between the top surface of the sample immersed in the mixed solution and the liquid surface of the mixed solution is at least 2 mm.

[0014] The chemical reagents used in this method are easy to obtain, the experimental process is easy to operate, and the properties of the solution after configuration are relatively stable and have a long shelf life. The solution has a significant effect on the columnar crystal area, equiaxed crystal area, and mixed crystal area in the ingot. When it is found that the dendrite has a significantly different morphological change, it can be determined that the solidification structure type here has changed; this method plays a role in regulating the corrosion of the ingot, is scientific and timely, and avoids the artificial differences caused by different corrosion time, heating time, solution concentration, etc., and can clearly determine the solidification structure type of SPHC low-carbon steel slabs. Embodiment 1

[0015] Slab continuous casting produces SPHC steel grades with a casting speed of 1.4m / min, a mold current of 300A, and a billet size of 920mm×200mm.

[0016] 1) Place the heater on the first weighing device, and the first beaker on the heater. Place two sizes of small blocks at the bottom of the heater for support, so that the first beaker is tilted, and ensure that the protruding opening of the first beaker is located at the bottom of the upper edge of the first beaker. Place the second beaker on the second weighing device, and then use a silicone hose to set the protruding opening of the first beaker. One end of the silicone hose is connected to the upper end of the condenser, and the bottom end of the condenser is located directly above the second beaker. Grind and polish the side of the sample that needs to be observed until the surface is bright, smooth and free of stains; 2) Add 200ml of deionized water to a beaker, heat it to 50°C using a heating device, then add 10g of anhydrous copper chloride and 100ml of 35% hydrochloric acid (AR (Shanghai test) grade) to the beaker, and stir until the mixed solution is uniform; if all the chemicals are directly added to the deionized water at the beginning, the copper chloride may be oxidized during the heating process and consume the hydrochloric acid instead, and the hydrochloric acid is volatile and has serious loss, and cannot fully react with the surface of the ingot. In order to match the amount of corrosion solution used, the sample size is specified as 100mm×60mm×20mm; 3) Add the sample to the heated mixed solution, requiring the sample surface to be immersed at least 2mm above the mixed solution surface to prevent some of the solution from failing to reach the sample surface during boiling; cover the top of the first beaker with a glass plate, silicone pad or other waterproof sheet to cover the surface of the beaker. The protruding notch of the beaker serves as an exhaust and condensation outlet. The beaker always maintains an overall high temperature atmosphere, thereby accelerating the overall erosion efficiency; at this time, start recording the data displayed by the weighing device. See the erosion mechanism for details. Figure 2 ; 4) Use a heating device to heat the sample, keep the temperature above 80°C, and keep the liquid surface boiling. The heating time should be more than 30 minutes. Copper chloride will produce a replacement reaction with iron atoms, and a copper film will be covered on the surface of the sample. The boiling mixed solution will take a long time to wash the copper film and break it, exposing the corrosion surface of the sample. Every 10 minutes, calculate the difference between the weight loss on the weighing table and the weight increase in the small-scale beaker. This is the weight of the lost hydrogen. Calculate the required amount of hydrochloric acid and add the required hydrochloric acid to the beaker to keep the concentration of the corrosion solution as much as possible. 5) Rinse the eroded sample with clean water for more than 1 minute. After cleaning, spray alcohol on the surface of the sample and blow dry it with a hair dryer to prevent surface oxidation contamination; 6) Take a photo of the sample to show the corrosion surface condition at a macroscopic level and record the image. Figure 3 ; Figure 3 Columnar crystals, white bright bands, and equiaxed crystal areas can be clearly seen. The area where the white bright band breaks the columnar crystals is defined as the mixed crystal area. Therefore, the equiaxed crystals and the mixed crystal area develop alternately into the ingot. The area where the central columnar crystals completely disappear is the equiaxed crystal area. 7) Use an optical microscope to observe and check the growth of dendrites, and pay special attention to the dendrite change area for recording; starting from the edge of the ingot, the dendrites grow vertically along the inner-outer arc, and their solidification structure is columnar crystals until the dendrite growth direction deflects and breaks; if the columnar crystals are constantly interrupted by abnormal tissues during their development inward, but the development direction of the columnar crystals remains unchanged, the abnormal tissues can be regarded as white bright bands; at the center of the ingot, the columnar crystals completely disappear, and the solidification structure enters the equiaxed crystal zone. Embodiment 2

[0017] Slab continuous casting produces SPHC steel grades with a casting speed of 1.4m / min, a mold current of 150A, and a slab size of 920mm×200mm.

[0018] 1) Place the heater on the first weighing device, and the first beaker on the heater. Place two sizes of small blocks at the bottom of the heater for support, so that the first beaker is tilted, and ensure that the protruding opening of the first beaker is located at the bottom of the upper edge of the first beaker. Place the second beaker on the second weighing device, and then use a silicone hose to set the protruding opening of the first beaker. One end of the silicone hose is connected to the upper end of the condenser, and the bottom end of the condenser is located directly above the second beaker. Grind and polish the side of the sample that needs to be observed until the surface is bright, smooth and free of stains; 2) Add 200ml of deionized water to a beaker, heat it to 50°C using a heating device, then add 10g of anhydrous copper chloride and 100ml of 35% hydrochloric acid (AR (Shanghai test) grade) to the beaker, and stir until the mixed solution is uniform; if all the chemicals are directly added to the deionized water at the beginning, the copper chloride may be oxidized during the heating process and consume the hydrochloric acid instead, and the hydrochloric acid is volatile and has serious loss, and cannot fully react with the surface of the ingot. In order to match the amount of corrosion solution used, the sample size is specified as 100mm×60mm×20mm; 3) Add the sample to the heated mixed solution, requiring the sample surface to be immersed at least 2mm above the mixed solution surface to prevent some of the solution from failing to reach the sample surface during boiling. Cover the top of the heating container (such as a beaker) with a glass plate, silicone pad or other waterproof sheet to cover the surface of the beaker. The protruding notch of the beaker serves as an exhaust and condensation outlet. The beaker always maintains an overall high-temperature atmosphere, thereby accelerating the overall erosion efficiency. At this time, start recording the data displayed by the weighing device. See the erosion mechanism for details. Figure 2 ; 4) Use a heating device to heat the sample, keep the temperature above 80°C, and keep the liquid surface boiling. The heating time should be more than 30 minutes. Copper chloride will produce a replacement reaction with iron atoms, and a copper film will be covered on the surface of the sample. The boiling mixed solution will take a long time to wash the copper film and break it, exposing the corrosion surface of the sample. Every 10 minutes, calculate the difference between the weight loss on the weighing table and the weight increase in the small-scale beaker. This is the weight of the lost hydrogen. Calculate the required amount of hydrochloric acid, and then add the required hydrochloric acid to the beaker to keep the concentration of the corrosion solution as much as possible. 5) Rinse the eroded sample with clean water for more than 1 minute. After cleaning, spray alcohol on the surface of the sample and blow dry it with a hair dryer to prevent surface oxidation contamination; 6) Take a photo of the sample to show the corrosion surface condition at a macroscopic level and record the image. Figure 4 ; Figure 4 There is water accumulation on the inner arc side of the casting, and the growth of columnar crystals on the outer arc side is hindered by grain deposition. The growth rate of columnar crystals on the inner arc side is faster. Therefore, the dendrites in the inner arc area of ​​the casting billet are mainly columnar crystals. The electromagnetic stirring has little effect here, and the larger columnar crystals cannot be broken. The white bright band appears in the columnar crystal area. The dendrite morphology at the outer arc position in the center of the casting billet is mainly equiaxed crystals, and the white bright band near the outer arc area gradually disappears along the width direction of the casting billet. Except for the only white bright band, the dendrite morphology is columnar crystals. 7) Observe with an optical microscope; starting from the edge of the ingot, the dendrites grow vertically along the inner-outer arc, and their solidification structure is columnar crystals until the dendrite growth direction deflects and breaks; if the columnar crystals are continuously interrupted by abnormal structures on the way to the inside, but the direction of columnar crystal development remains unchanged, the abnormal structures can be seen as white bright bands; at the center of the ingot, the columnar crystals completely disappear, and the solidification structure enters the equiaxed crystal zone.

Claims

1. A method for determining the solidification structure type of SPHC low carbon steel slab, characterized in that: The steps include: Step 1: Cut the sample into square blocks, and then grind and polish the side of the sample that needs to be observed until the surface is bright, flat, and free of stains to prevent excessive or insufficient erosion of the sample during the experiment; Step 2: Place the heater on the first weighing device, and place the first beaker on the heater, place two sizes of small blocks at the bottom of the heater for support, so that the first beaker is tilted, and ensure that the protruding opening of the first beaker is located at the bottom of the upper edge of the first beaker, place the second beaker on the second weighing device, and then use a silicone hose to set the protruding opening of the first beaker, one end of the silicone hose is connected to the upper end of the condenser, and the bottom end of the condenser is located directly above the second beaker; Step 3: Place two small blocks of different sizes at the bottom of the sample to ensure that the polished surface of the top of the sample is horizontal after it is placed in the first beaker; Step 4: Add deionized water to the first beaker and heat it, then add anhydrous cupric chloride and 35% hydrochloric acid, stir evenly, and then put the sample into the mixed solution; Step 5: Use a heater to heat the first beaker, requiring the liquid surface to remain boiling for a period of time. During this period, copper chloride will undergo a replacement reaction with iron atoms, and a layer of copper film will be covered on the surface of the sample. The boiling mixed solution will take a long time to flush the copper film, causing it to break and expose the corrosion surface of the sample; calculate the difference in the quantities measured by the two weighing devices at regular intervals, and then calculate the amount of hydrochloric acid that needs to be added, and then add hydrochloric acid to the first beaker; Step 6: Take out the eroded sample and rinse it with clean water for more than 1 minute. After cleaning, spray alcohol on the surface of the sample and blow dry it with a hair dryer to prevent oxidation contamination on the surface of the sample; Step 7: Take photos of the eroded samples to show the corrosion surface conditions at a macroscopic level. Use an optical microscope to observe and check the growth of dendrites, and focus on observing the dendrite change area for recording. Starting from the edge of the ingot, the dendrites grow vertically along the inner-outer arc, and their solidification structure is columnar crystals until the dendrite growth direction deflects and breaks. If the columnar crystals develop inward and are interrupted by abnormal tissues, but the development direction of the columnar crystals remains unchanged, the abnormal tissues can be seen as white bright bands. At the center of the ingot, the columnar crystals completely disappear, and the solidification structure enters the equiaxed crystal zone.

2. The method for determining the solidification structure type of SPHC low carbon steel slab according to claim 1, characterized in that: In step 4, 200 ml of deionized water is added to the first beaker. After the deionized water is heated to 50°C, 10 g of anhydrous copper chloride and 100 ml of 35% hydrochloric acid are added to the first beaker and stirred until the mixed solution is uniform. After the sample is added to the heated mixed solution, the position is adjusted so that the top surface of the sample is horizontal. The top of the first beaker is covered with a waterproof plate such as a glass plate or a silicone pad to cover the surface of the beaker. The protruding notch of the beaker is used as an exhaust and condensation outlet. The first beaker always maintains an overall high temperature atmosphere, thereby accelerating the overall corrosion efficiency. At this time, the data displayed by the weighing device is recorded.

3. The method for determining the solidification structure type of SPHC low carbon steel slab according to claim 1, characterized in that: In step five, when the heater heats the first beaker, the temperature of the mixed liquid in the first beaker is maintained above 80°C, and the heating time needs to be more than 30 minutes. The difference between the weight reduction measured by the first weighing device and the weight increase measured by the second weighing device is calculated every 10 minutes. This data difference is the weight of the lost hydrogen. The amount of hydrochloric acid required to be added is calculated based on the weight of the lost hydrogen, and then the hydrochloric acid is added to the first beaker to maintain the concentration of the corrosive solution as much as possible.

4. The method for determining the solidification structure type of SPHC low carbon steel slab according to claim 1, characterized in that: In step 4, the distance between the top surface of the sample immersed in the mixed solution and the liquid surface of the mixed solution is at least 2 mm.

Citation Information

Patent Citations

  • Method for measuring 14C in biological sample

    CN104062674A

  • Etching agent for displaying solidification dendritic structures of middle-high grade non-oriented silicon steel as well as etching method

    CN105200429A

  • Corrosive for flow line displaying under heading state of high-temperature alloy and corrosion testing method

    CN105543947A

  • Method for determining iron soap content in emulsion

    CN106680134A

  • Austenitic stainless steel welding seam structure corrosive agent and application method thereof

    CN107843592A